Environmental fate studies with 14C-polyoxyethylene tallow amine (POE-T) to characterize environmental exposure and inform environmental risk assessments. (May 2022) - Kurtzweil, Mitchell L.; Bleeke, Marian S.; Shepard, Michael R.
Abstract: Polyoxyethylene tallow amine (POE-T) is a member of the polyoxyethylene alkylamine (POEA) class of nonionic surfactants and is a component of some glyphosate-based formulations. The presence of POE-T improves foliar uptake of glyphosate in weeds, thereby reducing the amount of glyphosate needed for weed control. To further characterize the environmental fate of POE-T, aerobic soil degradation, hydrolysis, adsorption/desorption, and aerobic aquatic degradation studies were conducted according to U.S. EPA and OECD pesticide regulatory testing guidelines. POE-T labeled with carbon-14 was used in the studies to aid in analysis, assess mineralization to CO2, and allow for mass balance determinations. The aerobic soil half-lives (DT50 ) for POE-T ranged from 20 to 166 days with DT50 values increasing with increasing soil percent organic carbon (OC). POE-T was hydrolytically stable at pH 4–9. POE-T adsorbed strongly to soil ( K F o c a d s  = 17, 600–114, 000) with sorption generally increasing as soil percent OC increased. The aerobic aquatic (water-sediment) system DT50 s for POE-T were 14–29 days, with POE-T dissipating from the water column with DT50 s of 0.10–0.12 days through metabolism and adsorption to sediment. Based on these results, aquatic organisms are unlikely to be exposed to POE -T in the water column for more than a few hours following waterborne exposure and sediment is a significant sink for POE-T in aquatic systems. However, bioavailability of POE-T in sediment and soil is predicted to be low based on strong adsorption and it is not readily desorbed. Graphical abstract: Image 1 Highlights: Degradation through microbial activity occurs in soil and water-sediment systems Adsorption to soil and sediment is strong Dissipation from the water column of water-sediment systems is rapid Exposure is expected to be acute in water columns Bioavailability is expected be low in sediment or soil